The Influence of Capillary Pressure on Permeability in Rock Samples Using the Mercury Injection Capillary Pressure (MICP) Method - Nugroho, Nurkhozin Adhi; Agriandita, Isnani; Yuda, Farhan Bintang (Journal of Physics and Its Applications, 2024)
The Mercury Injection Capillary Pressure (MICP) method to measure capillary pressure has become a crucial technique for characterizing the porosity and permeability of reservoir rocks. This study aims to assess the impact of capillary pressure on the permeability of two rock samples from the Bangko and Telisa formations in the Central Sumatra basin. Measurements were conducted utilizing the Autopore V 9600 instrument, which employed mercury as the injected fluid into the two rock samples, under pressures reaching up to 60,000 psi. These pressures are classified as capillary pressure. The data obtained were analyzed through Drainage curves to elucidate the relationship between capillary pressure and permeability. The results derived from the Drainage curves indicate that the A1 rock sample from the Bangko formation has medium permeability, with displacement pressure (Pd) of 10.4871 psi. In comparison, the A2 sample from the Telisa formation has low permeability with Pd of 516.6259 psi. The increase in capillary pressure resulted in a decrease in water saturation and an increase in the intrusion of the non-wetting fluid (mercury), particularly in samples with better permeability. This finding suggests that lower Pd values indicate better pore connectivity, which correlates with increased permeability. Highlights that the MICP method provides profound insights into the relationship between capillary pressure and the ability of rocks to transmit fluids, as well as the significance of pore geometry and distribution in influencing the permeability characteristics of reservoir rocks.